Optimization of Cr(VI) Adsorption on Eugenol-Silica Gel Composites Using Behnken Box Design - Fathurrahman, Muhammad; Sutanto, Sutanto; Aminingsih, Tri; Maharani, Restu Dewinta (Jurnal Kartika Kimia, 2022)
This study aims to find the optimum conditions for the adsorption of Cr (VI) ion to the eugenol-silica gel composite as an adsorbent and to determine the adsorption parameters using the Langmuir and Freundlich isotherm model. The three optimization parameters analyzed were pH, contact time, and weight of the adsorbent of the eugenol-silica gel composite. The optimization experiment was designed using the Box Behnken Design Response Surface Methodology (RSM) on the MINITAB software. Then, the maximum adsorption capacity was evaluated using the Langmuir and Freundlich isotherm equation model. The results showed that the optimum conditions for the adsorption process were the weight of the eugenol-silica gel composite adsorbent of 0.15 grams, contact time of 35 minutes and pH of 5. The adsorption process under these conditions was favorable because the RL obtained was 0.0297. The maximum absorption capacity of Cr (VI) was indicated by the qm value of 1.0328 mg/g, and the KF, KL, and n values ​​observed 0.7961, 1.0885 and 14.0056, respectively. Adsorption of Cr(VI) ion by eugenol-silica gel composite followed the Langmuir isotherm equation.